Music of Today Garth Knox Viola & Viola d'amore February 22, 2016 - Watras, Melia; Barrett, Alessandra; Chalasani, Vijay; Fitzpatrick, Luke; Franz, Gwen; Pokorny, Emmeran; Kronos String Quartet (University of Washington School of Music, 2016)
Music of Today Garth Knox Viola & Viola d'amore February 22, 2016
Concert Program